Analisis Pasal TPPO dalam Kasus Ferienjob: Peran Lembaga Internasional dan Organisasi Kemanusiaan - Tsania Nuha Alfani (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
Ferienjobs are part-time jobs done during holiday periods, and are not a form of internship but rather a part of the job market. The Ferienjob case in Germany underlies the application of the Human Trafficking Crime article because this practice is detrimental and violates human rights. The research methodology used is a normative juridical approach. The aim of this research is to determine the elements that form the basis for the application of the article on the Crime of Human Trafficking in the Ferienjob case as well as the role of international institutions in the issue of criminal acts of human trafficking.